Financial Literacy and Retirement Planning in the Informal Sector in Kenya - Githui, Thomas; Ngare, Philip (My University, 2014)
Old age dependency has become a major issue of concern to governments today. This is because a large number of retirees lack any form of regular income to sustain them in retirement. Kenya has one of the highest levels of old age dependency currently estimated at 56%. The purpose of this study was to establish the impact of financial literacy on retirement planning in the informal sector in Kenya. The study found that financial literacy remains low in Kenya. Financial literacy was found to have a positive impact on retirement planning; however the results indicate that other factors such as income levels, age, marital status and level of education are also strongly related to retirement planning. Gender was found to have no impact on retirement planning. The study established that the probability of a financially illiterate person having no retirement planning is significantly high calling for increased investment in financial literacy programs to reverse the trend. The study recommends the development of a curriculum on financial education and pension education in middle level and higher learning institutions as well as community pension awareness programs such as road-shows and aggressive advertising campaigns to enlighten the people on importance of retirement planning
Keywords: Retirement planning; Financial literacy; Pensions